KIDNEY DISEASE SYMPTOMS AND TREATMENT OF ULTRA-HEALTH - Rakhmonov Bakhrom Bakhtiyorovich (TADQIQOTLAR.UZ, 2024)
Abstract: Kidney diseases in men and women include various pathologies that prevent  the  normal  functioning  of  these organs  of  the  urinary  system.  Each  of  the kidney  diseases  has  its  own  characteristics,  different  clinical  manifestations  and treatment methods. In fact, many kidney diseases are asymptomatic, that is, they occur without  symptoms,  and  patients  are  not  aware  of  the  existing  problems  with  their health. Therefore, it is important to understand what the main kidney diseases are, know their symptoms and treatment.